Managing depression in primary health care centers: The highlights of the program and further improvements - Herlina Siwi Widiana; Lenore Manderson; Katrina Simpson (Universitas Ahmad Dahlan, 2020)
Many people with probable depression present at primary health care centers (PHC) with physical complaints. Clinical psychologists (CPs) in Sleman district and Yogyakarta city, Special Province of Yogyakarta, Indonesia, have been integrated into PHC to provide psychological services. The study on which we draw aimed to explore how depression is managed in PHC. Thirty four CPs and twenty people diagnosed with mild to moderate depression participated in semi-structured interviews. Based on the thematic analysis of their transcribed interviews, seven themes emerged: community education and support, referral pathways, assessing depression, diagnosis, communicating a diagnosis, accepting diagnosis, and treatment of depression. The co-location of CPs with other medical services at the PHC level supports community understandings of mental health problems. It also encourages community members to use PHC services and to have access to various behavioral interventions for people with depression. Recommendations and directions for further research are discussed.